Linear peptide specificity of bovine antibody responses to p67 of Theileria parva and sequence diversity of sporozoite-neutralising epitopes: Implications for a vaccine - Nene, Vishvanath M.; Gobright, E.I.; Bishop, Richard P.; Morzaria, S.P.; Musoke, A.J. (American Society for Microbiology, 1999)
A stage-specific surface antigen of Theileria parva, p67, is the basis for the development of an anti-sporozoite vaccine for the control of East Coast fever (ECF) in cattle. By Pepscan analysis with a series of overlapping synthetic p67 peptides, the antigen was shown to contain five distinct linear peptide sequences recognized by sporozoite-neutralizing murine monoclonal antibodies. Three epitopes were located between amino acid positions 105 to 229 and two were located between positions 617 to 639 on p67. Bovine antibodies to a synthetic peptide containing one of these epitopes neutralized sporozoites, validating this approach for defining immune responses that are likely to contribute to immunity. Comparison of the peptide specificity of antibodies from cattle inoculated with recombinant p67 that were immune or susceptible to ECF did not reveal statistically significant differences between the two groups. In general, antipeptide antibody levels in the susceptible animals were lower than in the immune group and neither group developed high responses to all sporozoite neutralizing epitopes. The bovine antibody response to recombinant p67 was restricted to the N- and C- terminal regions of p67, and there was no activity against the central portion between positions 313 and 583. So far, p67 sequence polymorphisms have been identified only in buffalo-derived T. parva parasites, but the consequence of these for vaccine development remains to be defined. The data indicate that optimizations of the current vaccination protocol against ECF should include boosting of relevant antibody responses to neutralizing epitopes on p67.